Acoustic and archival technologies join forces: A combination tag. Issue 3 (10th January 2023) - Goossens, Jolien; Woillez, Mathieu; LeBris, Arnault; Verhelst, Pieterjan; Moens, Tom; Torreele, Els; Reubens, Jan
Abstract: Technological advances are key to maximizing the information potential in electronic tagging studies. Acoustic tags inform on the location of tagged animals when they are in the range of an acoustic receiver, whereas archival tags render continuous time series of logged sensor measurements, from which trajectories can be inferred. We applied a newly developed acoustic data storage tag (ADST) on 154 animals of three fish species to investigate the potential of this combination tag. Fish trajectories were reconstructed from logged depth and temperature histories using an existing geolocation modelling approach, adapted to include a likelihood for acoustic detections. Out of 126 detected fish (accounting for over 700, 000 detections) and 25 tag recoveries, eight ADSTs rendered both acoustic and archival data. These combined data could validate that the original geolocation model performed adequately in locating the fish trajectories in space. The acoustic data improved the timing of the daily position estimates. Acoustic and archival tagging technologies provided highly complementary information on fish movement patterns and could partly overcome the limitations of either technique. Furthermore, the ongoing developments to acoustically transmit summary statistics of logged data would further increase the information potential of combination tags when tracking aquatic species.